Effect of a Mandibular Advancement Device on the Upper Airway in a Patient with Obstructive Sleep Apnea - Flores-Orozco, Elan Ignacio; Tiznado-Orozco, Gaby Esthela; Díaz-Peña, Rogelio; Orozco, Esteban Isaí Flores [UNESP]; Galletti, Cosimo; Gazia, Francesco; Galletti, Francesco (Wolters Kluwer, 2019)
The authors present a case of a 33-year-old male patient with obstructive sleep apnea syndrome who was treated with a mandibular advancement device with excellent results. The aim of this study is to underline the importance of new instruments that allow evaluating the upper airway with greater precision, such as cone beam tomography. Given the diagnosis and treatment, the upper airway was assessed using cone beam tomography; an increase in UA volume of 22% was observed (initial volume 22,962 mm3), along with a 28% increase in area (initial area 971 mm2). The evaluation of the UA using teleradiography also showed an increase in the points evaluated, with the midpoint of the soft palate presenting the greatest increase.
Keywords: Cone beam tomography; mandibular advancement device; OSAS; upper airway